Acute kidney injury in children with cancer admitted in an intensive care unit - Almeida, Jáder Pereira; Luiz, Gabriela Caus Fernandes; De-Oliveira, Scheilla Torres; De-Santa, Larissa Nicolini; Borsato, Giovanna Soldatelli; João, Paulo Ramos David (Brazilian Journal of Oncology, 2022)
Objective: Evaluating the association between acute kidney injury and death in critically ill children with oncological diseases admitted in an intensive care unit (ICU).Material and Methods: Unicentric cohort study, evolving children with cancer admitted in the ICU of a pediatrics referral hospital. The patients were divided according to the presence or absence of acute kidney injury. Patients with a history of urogenital disease, nephrectomy or chronic kidney disease were excluded. The acute kidney injury was defined by the Kidney Disease Improving Global Outcomes (KDIGO) classification. The main outcome was death.Results: The sample was composed of 84 patients, in which 46.4% were diagnosed with hematologic neoplasm, 29.8% evolved with febrile neutropenia, 11.9% had a history of bone marrow transplant, and 27.3% deceased. Acute kidney injury occurred in 51.2% of the sample, 53.6% used furosemide, 38% showed fluid overload, and 8.3% had renal replacement therapy. The main variables related to kidney dysfunction were admission due to hemodynamic shock, pediatric risk of mortality score 2 ≥5%, bone marrow transplant, volume overload and multiple organ dysfunction syndrome. More advanced stages of acute kidney injury were associated with renal replacement therapy (p<0.001), longer stay in the ICU (p=0.006), and death (p=0.003).Conclusion: Children with cancer showed many risk factors of acute kidney injury, and this complication is associated with higher death rate.
Keywords: Acute kidney injury; Pediatric intensive care units; Medical oncology; Child; Multiple organ failure